Changes in the fermentation products, taxonomic and functional profiles of microbiota during high-moisture sweet sorghum silage fermentation - Zhao, Jie; Yin, Xue-Jing; Wang, Si-Ran; Li, Jun-Feng; Dong, Zhi-Hao; Shao, Tao (Frontiers in Microbiology, 2022)
The purpose of this study was to evaluate the fermentation quality, microbial community, and functional shifts of sweet sorghum during ensiling. The high-moisture sweet sorghum (SS) was naturally ensiled for 1, 3, 7, 15, 30, and 60 days. After 60 days of ensiling, sweet sorghum silage (SSS) showed homolactic fermentation with absent butyric acid, low pH value, acceptable concentrations of propionic acid, ethanol, and ammonia nitrogen and high lactic acid concentration. Acinetobacter, Sphingomonas, and Pseudomonas were the advantage genera in SS. While, Lactococcus, Weissella, and Pediococcus were dominant in 3-day SSS and subsequently replaced by Lactobacillus in 60-day SSS. Spearman’s correlation heatmap showed that Pediococcus and Leuconostoc were negatively related to the pH value of SSS. There were great differences in the Kyoto Encyclopedia of Genes and Genomes (KEGG) functional profiles of SS and SSS. Ensiling process downregulated the metabolism of amino acid, energy, cofactors, and vitamins, but upregulated the metabolism of nucleotides and carbohydrates. Overall, next-generation sequencing in conjunction with KEGG functional prediction revealed the distinct differences in the initial and late phases of ensiling in terms of both community succession and functional shifts. The knowledge regarding bacterial community dynamics and functional shifts of SS during ensiling is important for understanding the fermentation mechanism and may contribute to the production of high-quality sweet sorghum silage.